2009
DOI: 10.1186/1471-2105-10-433
|View full text |Cite
|
Sign up to set email alerts
|

Using mechanistic Bayesian networks to identify downstream targets of the Sonic Hedgehog pathway

Abstract: BackgroundThe topology of a biological pathway provides clues as to how a pathway operates, but rationally using this topology information with observed gene expression data remains a challenge.ResultsWe introduce a new general-purpose analytic method called Mechanistic Bayesian Networks (MBNs) that allows for the integration of gene expression data and known constraints within a signal or regulatory pathway to predict new downstream pathway targets. The MBN framework is implemented in an open-source Bayesian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…In contrast, if genes required continued exposure to SHH, they would remain downregulated in wild-type limb buds that received only a brief exposure to SHH. Although previous studies have identified SHH-responsive genes at E10.5 using microarrays (Probst et al, 2011; Shah et al, 2009), we decided to perform a new analysis using RNA-seq on E10.25 limb buds in order to make direct quantitative comparisons (Fig. 4A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, if genes required continued exposure to SHH, they would remain downregulated in wild-type limb buds that received only a brief exposure to SHH. Although previous studies have identified SHH-responsive genes at E10.5 using microarrays (Probst et al, 2011; Shah et al, 2009), we decided to perform a new analysis using RNA-seq on E10.25 limb buds in order to make direct quantitative comparisons (Fig. 4A).…”
Section: Resultsmentioning
confidence: 99%
“…Whole-genome approaches using DNA microarrays have been used to identify SHH-responsive genes during limb development (Bangs et al, 2010; Hu et al, 2012; McGlinn et al, 2005; Probst et al, 2011; Shah et al, 2009; Vokes et al, 2008). Combining this approach with three-dimensional spatial information from whole-mount embryo in situ hybridization has been successfully used to identify genes regulated in distinct domains (Bangs et al, 2010; Probst et al, 2011; Welten et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The Bayesian network analysis was performed using the Pebl software environment datasets ( http://jmlr.csail.mit.edu/papers/v10/shah09a.html ) [89] , [90] . All of the microarray datasets from wild-type and knockout mutants (n = 66) were used to define interactions in a 219 node network, which included the 208 core root epidermal genes, 7 genes representing knockout mutants but not part of the core genes, 2 hormone treatments (ACC and IAA), and 2 morphological characters (hair length and degree of hair branching).…”
Section: Methodsmentioning
confidence: 99%
“…In order to better discern organizational aspects of interacting networks of inflammatory mediators, such as coregulation or autoinduction, a variety of methods have been developed. Hierarchical clustering and Bayesian methods use high-throughput genomic or proteomic data of several time-points and/or conditions to correlate gene expression patterns with function and infer regulatory networks of correlated genes [34][35][36][37]. Focusing on the dynamics of inflammation, we used a simple network analysis method used over discrete intervals of data to analyse the commonality and differences between experimental surgical cannulation trauma þ haemorrhage in mice versus the sham procedure (surgical cannulation only) [25].…”
Section: Data-driven Modelsmentioning
confidence: 99%
“…A cohort of 10 000 virtual trauma patients was generated from the 33 patients' individual inflammatory and physiological trajectories. Each virtual patient was then subjected to three insults of trauma: low/intermediate Injury Severity Score (ISS) (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), intermediate/high ISS (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) and severe ISS (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50). The in silico distributions of model variables equated with length of stay in the intensive care unit, degree of multiple organ dysfunction and interleukin (IL)-6 area under the curve were in concordance with...…”
Section: Mechanistic Modelsmentioning
confidence: 99%